GUANO FERTILIZER APPLICATIONS TO IMPROVE GROWTH OF PALM OIL SEEDS (Elaeis guineensis Jacq) IN PRE-NURSERY - Seprita Lidar; Muryanto Muryanto (Universitas Lancang Kuning, 2020)
The study aims to determine the effect and get the best dose of guano fertilizer on the growth of oil palm seedlings in Pre Nursery conducted experimentally with a Completely Randomized Design (RAL) with 5 levels of treatment, 4 replications and 3 plants / plots with observational parameters are seed height, girth and number and leaf area. Observation data were analyzed statistically with variance and continued with Duncan test of 5% level. The application of guano fertilizer has a significant effect on plant height and leaf area, while the number of leaves and stem diameter has no significant effect. The 0.5 kg / polybag guano fertilizer treatment gave the best results to the growth of oil palm seedlings (Elaeis guineensis Jacq) in the pre-nursery.